2016
DOI: 10.3138/ptc.2015-59
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Composition and Sport Injury in Canadian Adolescents

Abstract: Purpose: To examine the association between overweight or obesity and sport injury in a population-based sample of Canadian adolescents. Methods: Cross-sectional analyses were performed using the Canadian Community Health Survey (2009–2010), a nationally representative sample (n=12,407) of adolescents aged 12–19 years. Body composition was quantified using BMI, grouping participants into healthy weight, overweight, or obese. The outcome of interest was acute or repetitive strain injury sustained during sport i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Unlike PA, body-related factors were not associated with medically attended injuries among adolescents. This aligns with the findings of Warsh et al ( 13 ) and Ezzat et al ( 14 ) showing no significant association of body composition with injury prevalence among adolescents. An explanation may regard the level of engagement in PA among adolescents; e.g., overweight or obese adolescents who lack the skill and confidence or have an insufficient CVF may not be able to cope with some sports situations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike PA, body-related factors were not associated with medically attended injuries among adolescents. This aligns with the findings of Warsh et al ( 13 ) and Ezzat et al ( 14 ) showing no significant association of body composition with injury prevalence among adolescents. An explanation may regard the level of engagement in PA among adolescents; e.g., overweight or obese adolescents who lack the skill and confidence or have an insufficient CVF may not be able to cope with some sports situations.…”
Section: Discussionsupporting
confidence: 92%
“…Richmond et al ( 12 ) found that the risk of sports injury in obese adolescents was higher than in adolescents with normal weight. Conversely, Warsh et al ( 13 ) and Ezzat et al ( 14 ) did not find evidence of a modifying effect of body composition on injury risk among adolescents. Furthermore, Carter and Micheli ( 15 ) and Watson et al ( 16 ) noted that well-developed CVF might protect youth from future injury.…”
Section: Introductionmentioning
confidence: 93%
“…Compared to research conducted in the university elite athletes, while the gender variable and Hootman et al's study data were similar and it was different from the results of the epidemiological research conducted by Yang et al 2,3 It has been reported that body composition is one of the main factors affecting performance and it is among the risk factors that can cause injury. 32 In our study, it was observed that body composition results were similar to the studies in the literature and athletes were in the ideal range in terms of body composition variables in the anthropometry title. In line with this, another reason why performances of athletes were not affected by the history of injury and fear of movement may be that they had an ideal body composition.…”
Section: Discussionsupporting
confidence: 87%
“…Contrastingly, Ezzat et al demonstrated in a cross-sectional study of 12 407 12–19 year-old that no significant association was found between being overweight and sports injury, but a protective effect was seen between obesity and sports injury instead 18. In a systematic review of sport climbing and bouldering by Woolings et al , higher BMI was reported to be associated with a higher risk of injury in one of the included studies but not found in two of the other included studies 19.…”
Section: Discussionmentioning
confidence: 84%